Identification of antifungal natural products via Saccharomyces cerevisiae bioassay: insights into macrotetrolide drug spectrum, potency and mode of action. (April 2013) - Tebbets, Brad; Yu, Zhiguo; Stewart, Douglas; Zhao, Li-Xing; Jiang, Yi; Xu, Li-Hua; Andes, David; Shen, Ben; Klein, Bruce
<x xml:space="preserve">Abstract</x> Since current antifungal drugs have not kept pace with the escalating medical demands of fungal infections, new, effective medications are required. However, antifungal drug discovery is hindered by the evolutionary similarity of mammalian and fungal cells, which results in fungal drug targets having human homologs and drug non-selectivity. The group III hybrid histidine kinases (HHKs) are an attractive drug target since they are conserved in fungi and absent in mammals. We used a Saccharomyces cerevisiae reporter strain that conditionally expresses HHK to establish a high-throughput bioassay to screen microbial extracts natural products for antifungals. We identified macrotetrolides, a group of related ionophores thought to exhibit restricted antifungal activity. In addition to confirming the use of this bioassay for the discovery of antifungal natural products, we demonstrated broader, more potent fungistatic activity of the macrotetrolides against multiple Candida spp., Cryptococcus spp., and Candida albicans in biofilms. Macrotetrolides were also active in an animal model of C. albicans biofilm, but were found to have inconsistent activity against fluconazole-resistant C. albicans, with most isolates resistant to this natural product. The macrotetrolides do not directly target HHKs, but their selective activity against S. cerevisiae grown in galactose (regardless of Drk1 expression) revealed potential new insight into the role of ion transport in the mode of action of these promising antifungal compounds. Thus, this simple, high-throughput bioassay permitted us to screen microbial extracts, identify natural products as antifungal drugs, and expand our understanding of the activity of macrotetrolides.